Activist-Research in Black: An Interdisciplinary, Transnational Roundtable (2019)
In this panel, a group of Black scholars gathers to discuss political, intellectual, and practical meanings of activist research in the Americas. Talking across the Atlantic, the authors generate responses to questions related to the following topics: knowledge and epistemological orientations, theory, positionality and power, and the alternatives in which socially-engaged research and change are offered. Calling on ruminations from research and personal experience, this article considers how Blackness augments the processes by which scholar activism has been created and understood by the authors. These comments seek to highlight not only the precarity in which such work is defined, but the opportunities that stand to be gained in understanding racial, sexual, and gendered elements of historical and contemporary social life through interdisciplinary and transnational perspectives.